Korelasi antara kontrol diri dengan kecenderungan agresi siswa - Hazniga Putri; Syaiful Bahri; Abu Bakar; Khairiah Asfaruddin (Program Studi Bimbingan dan Konseling, FKIP, Universitas Syiah Kuala, 2021)
The tendency to aggression is the desire to hurt others, both verbally and non-verbally. This desire often appears among teenagers and usually has a